The Protective Effect of Adiponectin-Transfected Endothelial Progenitor Cells on Cognitive Function in D-Galactose-Induced Aging Rats - Huang, Jing (Neural Plast, 2020)
Aging is a multifactorial process involving the cumulative effects of inflammation, oxidative stress, and mitochondrial dynamics, which can produce complex structural and biochemical alterations to the nervous system and lead to dysfunction of microcirculation, blood-brain barrier (BBB), and other problems in the brain. Long-term injection of D-galactose (D-gal) can induce chronic inflammation and oxidative stress, accelerating aging. The model of accelerated aging with long-term administration of D-gal have been widely used in anti-aging studies, due to the increase of chronic inflammation and decline of cognition that similarity with natural aging in animals. However, despite extensive researches in the D-gal-induced aging rats, studies on their microvasculature remain limited. Endothelial progenitor cells (EPCs), which are precursors to endothelial cells (ECs), play a significant role in the repair and regeneration process of endogenous blood vessel, and adiponectin (APN), a protein derived from adipocyte, has many effects on protective vascular endothelium and anti-inflammatory. Recently, many studies have shown that APN can promote improvements in cognitive function. Under these circumstances, we investigated the neuroprotective effect of the APN-transfected EPC (APN-EPC) treatment on rats after administration with D-gal and explored the likely underlying mechanisms. Compared to model group for D-gal administration, better cognitive function and denser microvessels were significantly found in the APN-EPC treatment group, and indicated APN-EPC treatment in aging rats could improve the cognitive dysfunction and microvessel density. The level of proinflammatory cytokines IL-1β, IL-6, and TNF-α, activated astrocytes and apoptosis rate were significantly reduced in the APN-EPC group compared with the model group, showed that APN-EPCs alleviated the neuroinflammation in aging rats. In addition, the APN-EPC group inhibited the decrease of BBB-related proteins claudin-5, occludin, and Zo-1 in aging rats and attenuated BBB dysfunction significantly. These results of our study indicated that APN-EPC treatment in D-gal-induced aging rats have a positive effect on improving cognitive and BBB dysfunction, increasing angiogenesis, and reducing neuroinflammation and apoptosis rate. This research suggests that cell therapy via gene modification may provide a safe and effective approach for the treatment of age-related neurogenerative diseases.